CULTURAL, MORPHOLOGICAL AND AFLATOXIGENIC VARIABILITY AMONG ISOLATES OF ASPERGILLUS FLAVUS FROM GROUNDNUT SEEDS (Journal of Plant Disease Sciences, 2017)
Twenty strains of (AF-1 to AF-20) were isolated from Aspergillus flavus the seeds of twenty different samples of groundnut. Studies on the cultural,  morphological and aflatoxigenic variability was done for all the isolates Isolates .  AF-9 and AF-18 belonged to the fast growing category (>50 mm colony diameter)  whereas; AF-5, AF-11, AF-16, AF-17 and AF-20 belonged to the slow growing  category (
Keywords: Aspergillus flavus, Groundnut, Aflatoxigenic variability